1997
DOI: 10.1002/(sici)1096-8652(199707)55:4<183::aid-ajh3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue factor pathway inhibitor in patients with acute myocardial infarction

Abstract: We examined hemostatic abnormalities in 23 patients with acute myocardial infarction (AMI), 10 with pulmonary embolism (PE), and 10 with deep vein thrombosis (DVT). At the onset of AMI, plasma levels of tissue-type plasminogen activator (t-PA), PA inhibitor-I (PAI-I), fibrin-D-dimer, thrombin-antithrombin complex (TAT), and plasmin-plasmin inhibitor complex (PPIC) were significantly increased. Both the plasma total TFPI and free-TFPI levels in the AMI patients were significantly higher than those in the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The amount of TFPI protein in the medium was measured by a 1-step sandwich ELISA method with human recombinant TFPI as a standard, as described previously. 18,24 The minimum amount of TFPI detectable by this method is 6.3 ng/mL.…”
Section: Replication-defective E1mentioning
confidence: 92%
See 1 more Smart Citation
“…The amount of TFPI protein in the medium was measured by a 1-step sandwich ELISA method with human recombinant TFPI as a standard, as described previously. 18,24 The minimum amount of TFPI detectable by this method is 6.3 ng/mL.…”
Section: Replication-defective E1mentioning
confidence: 92%
“…The amount of TFPI protein in the medium was measured by a 1-step sandwich ELISA method with human recombinant TFPI as a standard, as described previously. 18,24 The minimum amount of TFPI detectable by this method is 6.3 ng/mL.The vessels were harvested 4 weeks later, and 4 sections (5 m thick) were cut from the middle portion of each vessel. The cross-sectional areas of neointima and media were measured morphometrically with an automated computer-based image analyzer (DKC-5000, SONY) by a technician blinded to the treatment regimen.…”
mentioning
confidence: 99%
“…The secreted TFPI from monocytes and most vascular wall cells may be associated within plaque through the binding with proteoglycans and other TFPI binding protein on the cells (30,31). It has been reported in literature to be elevated in AMI patients (5,(7)(8)(9). Our results indicate increase levels in younger AMI patients while insignificant changes in the levels of plasma TFPI in elder AMI patients as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…As synthesis and secretion of TFPI is enhanced by heparin (32,33), it may have caused increase TFPI in Group 2 patients on treatment. Literature reports elevated levels in unstable angina patients (5,(34)(35)(36)(37) and marginal increase in case of stable angina patients (7). Moreover in our study we observed significant decrease in TFPI in AMI patients who had added risk factor of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known to activate factor X through intrinsic pathway by activating factor IX, leading to thrombin generation and fibrin formation. Since Suefuji et al in 1997 reported the role of TF in AMI, there have been many studies conducted to determine the status of plasma TF and AMI (Kamikura et al, 1997, Nishiyama et al, 1998, Malý et al, 2003, Morange et al, 2007, Xiong et al, 2007 with contradictory findings. We observed increased levels of TF in AMI at presentation (Shalia et al, 2010a).…”
Section: Tissue Factor (Tf)mentioning
confidence: 99%